2009
DOI: 10.2136/sssaj2008.0045
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Prediction of Soil Organic Matter Content Using Cokriging with Remotely Sensed Data

Abstract: Accurately measuring soil organic matter content (SOM) in paddy fields is important because SOM is one of the key soil properties controlling nutrient budgets in agricultural production systems. Estimation of this soil property at an acceptable level of accuracy is important; especially in the case when SOM exhibits strong spatial dependence and its measurement is a time‐ and labor‐consuming procedure. This study was conducted to evaluate and compare spatial estimation by kriging and cokriging with remotely se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 44 publications
0
31
0
6
Order By: Relevance
“…Th en, we compared the reliability in SOM estimation by the methods of kriging and cokriging based on the maps of kriging standard deviations, and validated them by using cross-validation. Th e detail processes and results are described in another paper (Wu et al, 2009). Th e results indicate that cokriging signifi cantly improved the precision and reliability of SOM prediction.…”
Section: Sampling Design and Soil Analysismentioning
confidence: 93%
“…Th en, we compared the reliability in SOM estimation by the methods of kriging and cokriging based on the maps of kriging standard deviations, and validated them by using cross-validation. Th e detail processes and results are described in another paper (Wu et al, 2009). Th e results indicate that cokriging signifi cantly improved the precision and reliability of SOM prediction.…”
Section: Sampling Design and Soil Analysismentioning
confidence: 93%
“…To reveal the spatiotemporal distribution and evolution characteristics of groundwater salinization, geostatistical methods prove to be of great power to predict and display the distribution, variation and relevancy of different variants by interpolation from points data, especially for ordinary kriging (OK) [47,48]. However, recent studies have shown that the interpolation results by OK were not accurate with relatively few data, and co-kriging (COK) could improve the predict results notably, while the independent variable was highly-correlated with the coordination variables [49][50][51]. Based on the CT results of major ions and TDS and comparing the results of the mean error (ME), mean-squared error (MSE) and mean-square standard error (MSSE) of interpolation results in cross-validation by OK and COK, COK is finally used to display the spatial distribution of groundwater TDS among decades to reflect the variation tendency of groundwater quality in the study area.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…A 0 is the absorbance in the bland test, which generally uses silica sand or burnt soil as the soil samples for comparison; and details of the calculation of SOM content are given elsewhere (e.g., [4,20]). The spectral reflectance (350-2500 nm) of the soil samples was measured using an ASD FieldSpec3 portable spectral radiometer.…”
Section: Sample Production and Spectral Measurementmentioning
confidence: 99%
“…is the absorbance in the bland test, which generally uses silica sand or burnt soil as the soil samples for comparison; and details of the calculation of SOM content are given elsewhere (e.g., [4,20]). …”
Section: = × 100mentioning
confidence: 99%
See 1 more Smart Citation